The Influence Of Breast Self-Exam Education Through Interactive Health Education On Knowledge, Attitudes, And Action Of Women Reproductive Age At The Health Education Training Center In Central Sulawesi Province - Natalia, Caroline; Nur, Rosmala; Fauzan, Fauzan; Sridani, Ni Wayan; Wahyuni, Rosa Dwi (Rifa'Institute, 2025)
Background: Background: In 2024, Central Sulawesi recorded 74 breast tumor cases, with Palu having the highest screening coverage and North Morowali the lowest. At the Health Training Center, only one of eight staff showed proper BSE knowledge and technique, indicating poor practice. These findings underscore the need for effective education to strengthen early breast cancer detection behaviors. Method: A quantitative approach with a quasi-experimental design was applied in August 2025. The study involved all 41 registered women of reproductive age (WRA) at the Health Training Center, selected through total sampling. Data analysis included univariate analysis for descriptive characteristics, paired sample t-test to assess pre–post intervention changes, and One Way ANOVA to identify differences between groups after receiving interactive educational sessions. Results: Findings from the paired sample t-test revealed significant improvements in knowledge, attitudes, and practices following the intervention (p < 0.05). ANOVA further showed significant differences across groups for all variables, with behavioral changes demonstrating the highest F-value. Interactive education involving demonstrations and hands-on practice effectively enhanced cognitive understanding, shaped positive attitudes, and strengthened participants’ ability to perform BSE consistently. Conclusion: Interactive BSE education significantly improved knowledge, attitudes, and practices among women of reproductive age, with direct practice serving as a vital component in sustaining behavior change. Recomendation: Routine interactive BSE training is advised to sustain skills and confidence, supported by efforts targeting women with low self-efficacy and strengthened collaboration with health cadres and facilities. Further research is needed to identify factors influencing long-term adherence.